Glaucoma and Ocular Surface Disease: More than Meets the Eye - Li G; Akpek EK; Ahmad S (Clinical Ophthalmology, 2022)
Gavin Li,1 Esen Karamursel Akpek,2 Sumayya Ahmad1 1Department of Ophthalmology at the Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2Ocular Surface Disease Clinic, Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, USACorrespondence: Sumayya Ahmad, New York Eye and Ear Infirmary, Icahn School of Medicine at Mount Sinai, 2520 30th Avenue, Long Island City, New York, NY, 11102, USA, Tel +1 (301)-473-3930, Fax +1 718-808-7757, Email sumayya.ahmad@gmail.comAbstract: Understanding the association between ocular surface disease and glaucoma is important for improving adherence to treatment and introducing practical solutions. While topical antihypertensive medications for glaucoma are well tolerated according to short-term studies, there is little evidence on their long-term effects. Since they are often required for many years, the effects of these drops on the ocular surface become important in regard to quality of life and adherence. In this nonsystematic review performed in April 2022, we summarize what is known about the relationship between glaucoma and ocular surface disease. Specifically, we examine how each class of topical glaucoma drops affects the ocular surface. We then review the treatment of ocular surface disease for patients on topical glaucoma therapy. Finally, we discuss treatments that may reduce or eliminate the burden of topical medications.Keywords: glaucoma, ocular surface disease, adherence